-7(v-3)=-5v+27

Simple and best practice solution for -7(v-3)=-5v+27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(v-3)=-5v+27 equation:


Simplifying
-7(v + -3) = -5v + 27

Reorder the terms:
-7(-3 + v) = -5v + 27
(-3 * -7 + v * -7) = -5v + 27
(21 + -7v) = -5v + 27

Reorder the terms:
21 + -7v = 27 + -5v

Solving
21 + -7v = 27 + -5v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '5v' to each side of the equation.
21 + -7v + 5v = 27 + -5v + 5v

Combine like terms: -7v + 5v = -2v
21 + -2v = 27 + -5v + 5v

Combine like terms: -5v + 5v = 0
21 + -2v = 27 + 0
21 + -2v = 27

Add '-21' to each side of the equation.
21 + -21 + -2v = 27 + -21

Combine like terms: 21 + -21 = 0
0 + -2v = 27 + -21
-2v = 27 + -21

Combine like terms: 27 + -21 = 6
-2v = 6

Divide each side by '-2'.
v = -3

Simplifying
v = -3

See similar equations:

| 3x^2-48x-18=0 | | -88=8(x-3) | | 7y-4.2=16.8 | | 4(x+7)-5=20 | | 2(x+6)=8x-5+2-6x | | 6k=32-2k | | .3(m+6)=4 | | 6y-2=-3x | | 6+6(7-9m)= | | 24=-11w-8+3w | | 20n+70=350 | | -2/3+3/8=x | | -2.6+10.2=x | | (x+1)+(4x-56)=180 | | a+2a+12=15a+8 | | 1.3(7x+5)=3x-5 | | -4.1+3.6=x | | 3*3-7[(3-8)-(-5-8)]= | | 38x+12=0 | | 35=7(2x-8) | | 2x^2-17x-55=0 | | 11+x=24 | | (8x+2)-(4x+1)= | | -33+6x=9 | | (15x-2y+5c)(2x-3y-c)=0 | | -2+v=6 | | (2x-3)(x-1)=0 | | y=5-15 | | 10p^2-8p=3 | | 6x^2-35x+49=0 | | 3-11a=-6 | | 9e^5t=12e^4t |

Equations solver categories